Research of the possibilities for small object detection using synthetic aperture radar - Stepanic, Josip; Bukljas, Zdravko (Proceedings of National Aviation University (archive), 1999)
Considered is the problem of detection of small objects which are lost or hidden in some landscape by means of synthetic aperture radar. The starting points are the possibility of real-time analysis and guarantee of precise, reliable and speedy evaluation